Nanocomposite Hydrogels: 3D‐Bioprinted Osteoblast‐Laden Nanocomposite Hydrogel Constructs with Induced Microenvironments Promote Cell Viability, Differentiation, and Osteogenesis both In Vitro and In Vivo (Adv. Sci. 3/2018). Issue 3 (25th March 2018) - Zhai, Xinyun; Ruan, Changshun; Ma, Yufei; Cheng, Delin; Wu, Mingming; Liu, Wenguang; Zhao, Xiaoli; Pan, Haobo; Lu, William Weijia
Abstract : In article number 1700550, Changshun Ruan, Haobo Pan, William Weijia Lu, and co‐workers report the development of an osteoblast‐laden nanocomposite hydrogel construct for bone regeneration. The construct is created using a two‐channel, 3D‐bioprinting method and exhibits high cell viability in the short term after bioprinting. In the long term, it is shown to have excellent osteogenic capabilities, both in vitro and in vivo, because of the bioactive ions that are gradually released.